A New Type of Multifunctional Polar Binder: Toward Practical Application of High Energy Lithium Sulfur Batteries. Issue 11 (6th February 2017) - Chen, Wei; Qian, Tao; Xiong, Jie; Xu, Na; Liu, Xuejun; Liu, Jie; Zhou, Jinqiu; Shen, Xiaowei; Yang, Tingzhou; Chen, Yu; Yan, Chenglin
Abstract : A new type of amino polar binder with 3D network flexibility structure for high energy Li–S batteries is synthesized and successfully used with commercial sulfur powder cathodes. The binder shows significant performance improvement in capacity retention and high potential for practical application, which arouse the battery community's interest in the commercial application of high energy Li–S battery.